(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Use of AI in the conduct of HR processes involves pitching upon the right data-driven decisions to strengthen the organisation and prepare biter for an uncertain future by eliminating errors in judgement and making the employee experience be more meaningful. By collaborating HR with AI, HR Department would be able to ensure higher level of accuracy with respect to all its processes such as recruitment and selection, compensation management, performance management and learning and development management. It would also help in reducing bias related to the HR processes which would result in ignoring employee related demographic information which typically results in unconscious bias while making vital decisions.